The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1093/brain/awaa245
|View full text |Cite
|
Sign up to set email alerts
|

Graded, multidimensional intra- and intergroup variations in primary progressive aphasia and post-stroke aphasia

Abstract: Language impairments caused by stroke (post-stroke aphasia, PSA) and neurodegeneration (primary progressive aphasia, PPA) have overlapping symptomatology, nomenclature and are classically divided into categorical subtypes. Surprisingly, PPA and PSA have rarely been directly compared in detail. Rather, previous studies have compared certain subtypes (e.g. semantic variants) or have focused on a specific cognitive/linguistic task (e.g. reading). This study assessed a large range of linguistic and cognitive tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 88 publications
3
39
0
Order By: Relevance
“…By evaluating a large cohort of patients suffering from stroke, neurodegenerative, and post-resective aphasia, we have provided a two-dimensional framework that can visualize language impairment across a variety of disease etiologies. While the language tool assessment shared across three cohorts highlights the similarities of aphasia phenotypes across disease etiologies, as with prior dimensionality reduction studies ( 22 ), the proposed framework using only two dimensions also provides sufficient granularity to preserve clinical classifications across all cohorts. This visual method of characterizing an aphasia phenotype provides a simplified and intuitive method of rapidly assessing aphasia phenotypes across populations and time.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…By evaluating a large cohort of patients suffering from stroke, neurodegenerative, and post-resective aphasia, we have provided a two-dimensional framework that can visualize language impairment across a variety of disease etiologies. While the language tool assessment shared across three cohorts highlights the similarities of aphasia phenotypes across disease etiologies, as with prior dimensionality reduction studies ( 22 ), the proposed framework using only two dimensions also provides sufficient granularity to preserve clinical classifications across all cohorts. This visual method of characterizing an aphasia phenotype provides a simplified and intuitive method of rapidly assessing aphasia phenotypes across populations and time.…”
Section: Discussionmentioning
confidence: 97%
“…The behavioral similarity mirrors the neuroanatomical similarity, in which peak atrophy for patients with nfvPPA localizes to the left posterior inferior frontal gyrus and adjacent areas ( 3 ). Investigation at higher dimensions or with more detailed behavioral assessments would enable discernment of behavioral differences ( 22 ). For instance, studies of nfvPPA have shown that grammar and fluency can be dissociated; case examples of patients with nfvPPA were found to have near normal fluency but impaired grammar and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations